2011
DOI: 10.1007/s00431-011-1417-6
|View full text |Cite
|
Sign up to set email alerts
|

Food allergy-related paediatric constipation: the usefulness of atopy patch test

Abstract: The aims of this study were to evaluate the implication of food allergy as a cause of paediatric constipation and to determine the diet period needed to tolerate the constipation-causing foods. Fifty-four children aged 6 months to 14 years (median, 42 months) suffering from chronic constipation (without anatomic abnormalities, cοeliac disease or hypothyroidism), unresponsive to a 3-month laxative therapy, were prospectively evaluated. All participants were evaluated for allergy to cow's milk, egg, wheat, rice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 21 publications
0
25
0
1
Order By: Relevance
“…Besinlerle yapılan APT, AD'de ön plana çıkmakla birlikte besinlere bağlı diğer alerjik durumlarda da tartışmalı bir tanı yöntemidir. Kronik konstipasyon nedeniyle besin alerjisi düşünülen çocuklarda besinlerle yapılan APT'nin IgE aracılıklı olmayan gıda alerjilerinin tespitinde ve eliminasyon diyetine karar verme konusunda yararlı bir tanı yöntemi olduğu bildirilmiştir 15 . Sonuç olarak inhalan allerjenlerle yapılan APT bile halen tam olarak standardize edilebilmiş değildir ve besinler için bu problem çok daha belirgindir.…”
Section: Discussionunclassified
“…Besinlerle yapılan APT, AD'de ön plana çıkmakla birlikte besinlere bağlı diğer alerjik durumlarda da tartışmalı bir tanı yöntemidir. Kronik konstipasyon nedeniyle besin alerjisi düşünülen çocuklarda besinlerle yapılan APT'nin IgE aracılıklı olmayan gıda alerjilerinin tespitinde ve eliminasyon diyetine karar verme konusunda yararlı bir tanı yöntemi olduğu bildirilmiştir 15 . Sonuç olarak inhalan allerjenlerle yapılan APT bile halen tam olarak standardize edilebilmiş değildir ve besinler için bu problem çok daha belirgindir.…”
Section: Discussionunclassified
“…Syrigou et al (34) showed that constipation improved in 28 of 32 children after an eight-week diet free of foods (wheat, egg, cow's milk, rice, corn, soy) whose specific IgE levels, skin prick tests, or atopy patch tests were positive. Twenty-seven responders had positive patch tests, and eight also had positive specific IgE and/or skin prick tests.…”
Section: Food Allergy and Fcmentioning
confidence: 99%
“…Constipation may result from a previous painful defecation, with the child avoiding defecation to avoid a repeat painful experience . Food allergy is also associated with functional constipation in children, with milk, egg, and wheat being the most common allergens associated with constipation . Dietary factors such as fluid and dietary fiber intake are contributors in the development of functional constipation …”
Section: Introductionmentioning
confidence: 99%